U-plant: a RFID-based ubiquitous plant learning system for promoting self-regulation. (8th June 2011) - Hsu, Jenq-Muh; Lai, Yen-Shou; Yu, Pao-Ta
This study, based on self-regulated learning, integrates with wireless networking and radio-frequency identification (RFID) to construct a smart ubiquitous plant learning environment. By using ubiquitous computing technologies, pupils can interact directly with the learning contents at the right place and at the right time through the ubiquitous plant learning system with non-contact RFID interaction. A total of 56 students of fifth grade in an elementary school participated in this study. The results showed that the experimental group outperformed than the control one in learning achievement. Using the information and communication technologies combing with self-regulated learning is helpful to enhance students' learning.